Pengaruh Pengasaman terhadap Fotodegradasi Klorofil a - Aji Wahyu Budiyanto; Soenarto Notosudarmo; Leenawaty Limantara (Jurnal Matematika & Sains, 2008)
Chlorophyll is tetrapyrole pigment, which is potential to be developed as photosensitizer agent on cancer photodynamictherapy. Its environments and properties during interaction are an important parameter to know the next fate of thesensitizer. Acidic environment is one of the key factors on cancerous patients. The research was carried out to determinethe acidification effect against photostability of chlorophyll a that was observed by its spectral pattern. Result showedthat titration of less than 250 Î¼L acetic acid 3 M caused degradation of chlorophyll a more rapidly. Volume and type ofacid properties did not only influenced pheophytinization reaction, but also caused pheophytin a to deaggregate, thatwas characterized by hypsochromic shift of Qy band.